The Interrelationship between Blood Glucose Values and Cellular Metabolism: A Review - Simon, Kornél; Cziráki, Attila (Medicine and Medical Research: New Perspectives Vol. 9, 2024)
This review aims to reveal additional insight into the relation between blood glucose value and cell metabolism and, furthermore to propose a more appropriate approach than blood glucose value for the assessment of cell metabolism. The persistence of functional and morphological integrity of living organisms is supported by cell metabolism, therefore its diagnostic assessment is of basic importance. The relationship between blood glucose value and cellular metabolism in stress reaction (a physiological state) and diabetes (a pathophysiological state) was investigated. Metabolism is considered the central physiological process of the living organism: therefore, the existence of metabolism can be referred to as the "marker of life". The study discusses metabolic characteristics of acute, repetitive, and chronic stress conditions respectively, and defines the terms: eumetabolism, dysmetabolism, and hypermetabolism with vs. without energetic equilibrium. In all chronic stress states persistence of the stressor triggering the stress reaction is emphasized as a harmful factor. Acute and repetitíve stress is referred to as a health-saving adaptive mechanism, but chronic stress with an energetic imbalance of cell metabolism is suggested as a health-threatening maladaptive phenomenon. Glucose toxicity is proposed as the main pathogenetic factor in eliciting and supporting chronic stress reactions. The interrelations between metabolic settings of diabetes, ischemia, and chronic stress, furthermore the metabolic effect of acute and chronic hyperglycemia (diabetes) on cell metabolism are discussed. Authors emphasize, that blood glucose value is of basic importance in determining the therapy of diabetes, but not in assessment of the cellular metabolic state. The rationale behind this statement is that blood glucose can really be referred to as a transport parameter, which reflects the actual equilibrium between glucose transport to the blood from the intestinal tract and glucose deposits, on the one hand, and glucose transport into peripheral tissues (glucose disposal) from blood, on the other hand. The relation between the trigger-specific somatic adaptation and the stressor-induced non-specific metabolic alterations is disputed. Authors suggest that metabolic characterization of acute, repetitive, and chronic stress states is a more reliable approach in the evaluation of cell metabolic state (referred to as „metabolic diagnosis”) than blood glucose determination related to blood glucose transport. Similarities of metabolic states of starvation, pregnancy, and SGLT2 inhibitor treatment are detailed as an example of the clinical application of „metabolic diagnosis”. Chronic stress with the preserved energetic balance of cell metabolism, characterized by glucopenic mild ketosis resulting in a unique cellular metabolic state of maximum energetic efficacy is emphasized. The distinct metabolic characteristics of acute, repetitive, and chronic stress reactions can be well described and their identification (the "metabolic diagnosis") provides a more accurate approach to defining the metabolic state of the organism compared to the determination of blood glucose values.